1983
DOI: 10.1161/01.res.52.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cost of the stimulated beating of isolated adult rat heart cells in suspension.

Abstract: SUMMARY. Heart cells from adult rats were induced to beat in suspension by electric field stimulation. We have gained evidence that all the rod-shaped cells in suspension were indeed beating, and that the beat had dynamic characteristics similar to those of intact heart muscle contracting under zero load. The cells were undamaged in the process, as judged by maintenance of ATP levels, morphology, and ability to beat. In gaining such evidence, we also measured the metabolic cost to the cells of beating under ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…The levels of FCCP used in that study, and in this one, are extremely low: the highest level, 6 pmol/mg, is approximately 50-fold less than the level required to uncouple oxidative phosphorylation completely. Since the basal metabolic rate of isolated cells, being quiescent, is very low (Haworth et al, 1983), addition of FCCP is a convenient means of increasing the metabolic demand in a controlled fashion to levels more typical of cells in a weakly beating anoxic heart. We have found that while glucose uptake is stimulated by conditions similar to anoxia, the extent of stimulation is curtailed if the metabolic demand is too high and this leads to contracture.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of FCCP used in that study, and in this one, are extremely low: the highest level, 6 pmol/mg, is approximately 50-fold less than the level required to uncouple oxidative phosphorylation completely. Since the basal metabolic rate of isolated cells, being quiescent, is very low (Haworth et al, 1983), addition of FCCP is a convenient means of increasing the metabolic demand in a controlled fashion to levels more typical of cells in a weakly beating anoxic heart. We have found that while glucose uptake is stimulated by conditions similar to anoxia, the extent of stimulation is curtailed if the metabolic demand is too high and this leads to contracture.…”
mentioning
confidence: 99%
“…Uncouplers also induce mitochondrial adenosine triphosphatase (ATPase) activity (Lardy and Wellman, 1953). FCCP in the presence of rotenone increases the rate of ATP utilization in isolated heart cells by stimulating this ATPase activity, and, since respiration is inhibited, the rate of lactate production is increased (Haworth et al, 1983). This increase is proportional to the amount of FCCP added, suggesting that, under these conditions, a unit increase in ATP demand is met by a unit increase in ATP supply (Haworth et al, 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, diffusion of lactate into the cytosol may interfere with ATP production via glycolysis, thereby depleting the ATP pool. The basal metabolic rate of quiescent myocytes is very low and glycolysis, as measured by the rate of lactate formation, is negligible (19). Therefore, under our experimental conditions, inhibition of glycolysis by lactate, if present, would minimally affect ATP production.…”
Section: Resultsmentioning
confidence: 77%
“…Furthermore, this model depends on contractile activity of the cells as neither mPTP opening nor cell death was observed in the absence of electrical stimulation. A plausible explanation is that the part of metabolic cost for contractile activity involves Ca 2+ and glucose availability (Haworth et al, 1983;Geisbuhler et al, 1983). It has been demonstrated that reducing oxygen and glucose concentrations of the hypoxic perfusate resulted in poorer recovery of the cardiomyocytes (Geisbuhler et al, 1990;Poizat et al, 1994).…”
Section: +mentioning
confidence: 99%